Effect of Cashew Nutshell Oil Supplementation as Phenol Source for Protein Protection on In Vitro Nutrient Digestibility - Rahma Fitriastuti; Lies Mira Yusiati; Budi Prasetyo Widyobroto; Zaenal Bachruddin; Chusnul Hanim (Faculty of Animal Science, Universitas Gadjah Mada, 2019)
The current study was aimed to evaluate the ability of phenol content in cashew nutshell liquid (CNSL) in binding protein and its effect on in vitro nutrient digestibility. This research divided into three steps, there were determination of total phenol and tannins content in CNSL, optimalization binding of CNSL tannin to bovine serum albumin with the determination of protein-percipitable phenolics compound and protein content using Lowry method, after that amount of optimalization supplementation of CNSL was used for measuring on in vitro nutrient digestibility by Tilley and Terry method. The results showed that phenol and tannin content of CNSL were 148.69 g/100 ml and 28.3 g/100 ml. One gram tannin in CNSL could be bound by 65.83 g protein. Optimum tannin were used in this study was 5.85 g tannin or equivalent to 163.91 mg of CNSL. Amount of CNSL were used in various levels, there are 0, 50, 100, 150 dan 200 mg. CNSL supplementation reduced dry matter, organic matter crude protein digestibility in rumen, and didn’t reduce dry matter dan crude protein in vitro post rumen digestibility. Supplementation of CNSL increased feed efficiency on in vitro.